Kemandirian Anak Dalam Pembelajaran Pengembangan Sosial Emosional (Studi Deskriptif Kuantitatif di PAUD Assalam Muara Bangkahulu Kota Bengkulu) - Suci Pangestu; Sri Saparahayuningsih; Delrefi D. (Jurnal Ilmiah POTENSIA, 2017)
The purpose of this study is to describe the independence of children in emotional social development learning in early childhood Assalam Muara Bangkahulu Bengkulu City. The type of research used in this study is quantitative descriptive research and data collection techniques through observation. Data analysis using statistics with the presentese formula. The subjects of this study were 18 children. The results showed that the independence of children in learning emotional social development of children in the group B2 PAUD Assalam Muara Bangkahulu City Bengkulu in good classification. The aspect is confidence in the classification of enough, while responsible, sociable, sharing, and controlling the average emotion in the good classification. It is advisable for further researchers to increase the child's confidence in emotional social development learning.